2009
DOI: 10.1007/s10886-009-9590-z
|View full text |Cite
|
Sign up to set email alerts
|

Caterpillar Footprints as Host Location Kairomones for Cotesia marginiventris: Persistence and Chemical Nature

Abstract: Herbivores walking over the epicuticular wax layer of a plant may leave tracks that disclose their presence to hunting predators or parasitoids. The braconid wasp Cotesia marginiventris is a solitary parasitoid of young noctuid caterpillars. It can locate potential hosts from a distance by orienting toward the scent of herbivore-damaged plants. Upon landing on the caterpillars' food plant, the female parasitoid searches for further cues (kairomones) that confirm the presence of a suitable host. In a previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…Additionally, unknown minor compounds as well as hostspecific volatiles also may play a role in differentiation of different host-plant complexes. Further discrimination may be mediated at short range by host contact kairomones (which are typically of relatively lower volatility), such as host feces (Loke and Ashley 1984;Dmoch et al 1985;Afsheen et al 2008) and caterpillar chemical footprints on infested plants (Rostas and Wölfling 2009). Future behavioral studies are necessary to confirm whether or not the ability of M. croceipes to distinguish between plants damaged by its host and non-host caterpillars (Rosé et al 1997), is in fact mediated by the subtle quantitative differences in volatile blends recorded in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, unknown minor compounds as well as hostspecific volatiles also may play a role in differentiation of different host-plant complexes. Further discrimination may be mediated at short range by host contact kairomones (which are typically of relatively lower volatility), such as host feces (Loke and Ashley 1984;Dmoch et al 1985;Afsheen et al 2008) and caterpillar chemical footprints on infested plants (Rostas and Wölfling 2009). Future behavioral studies are necessary to confirm whether or not the ability of M. croceipes to distinguish between plants damaged by its host and non-host caterpillars (Rosé et al 1997), is in fact mediated by the subtle quantitative differences in volatile blends recorded in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The non-polar CHCs have been extensively investigated over the past three decades with respect to their role as semiochemicals (Howard, 1993;Singer, 1998;Howard and Blomquist, 2005). A multitude of studies have shown that CHCs are not only involved in the diverse interactions of social insects (Greene and Gordon, 2003;Endler et al, 2004;van Zweden and d'Ettorre, 2010) but also used by many solitary insects as contact stimuli when searching for oviposition sites (Colazza et al, 2007;Rostas and Wolfling, 2009;Darrouzet et al, 2010) or sexual mates (Syvertsen et al, 1995;Sullivan, 2002;Steiner et al, 2005;Steiner et al, 2006;Sugeno et al, 2006;Geiselhardt et al, 2009;Ferveur and Cobb, 2010;Ginzel, 2010;Ruther et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be investigated for how long T. basalis can detect the chemical footprints of its host. Studies on a larval parasitoid showed that the wasps recognize footprints from caterpillars for a period of at least 2 days (Rostás and Wölfling, 2009). This suggests that these kairomones can be retained for a relevant length of time and should help to improve the efficiency in finding a suitable host.…”
Section: Discussionmentioning
confidence: 99%
“…Smith) (Lepidoptera: Noctuidae), when footprints that mainly consist of linear and monomethyl-branched alkanes are left on the leaf surface of either wild-type or eceriferum mutants of barley. The mutants were characterized by lower amounts of the main wax component hexacosanol and a high aldehyde fraction (Rostás et al, 2008;Rostás and Wölfling, 2009).…”
Section: Introductionmentioning
confidence: 99%